Preparation and high temperature thermal conductivity of UO2/SiC fully ceramic microencapsulated pellets - DUAN Limei; WANG Zhiyi; HUANG Qiqi; XIE Liang; HU Fengyun; ZHONG Yi; YANG Zhenliang; LI Bingqing; XU Jingkun; WANG Mingshan; GAO Rui; CHU Mingfu (Fenmo yejin jishu)
A series of UO2/SiC composite fully ceramic microencapsulated (FCM) pellets were prepared by self-grinding spheroidization coating and spark plasma sintering. The parameters, such as heating rate, sintering temperature, sintering pressure, and SiC content, were regulated. The phase composition and structural characteristics of the pellets were observed by metallographic microscopy and scanning electron microscopy. The thermal conductivity (TC) of the pellets from room temperature to 1200 ℃ was obtained by laser thermal conductivity meter. The effects of process parameters on the microstructure and TC of the pellets were discussed. The results indicate that, the UO2@SiC composite particles are nearly spherical and well coated. The SiC matrix in UO2/SiC composite pellets exhibits a three-dimensional interconnected network structure. The sintering pressure has a significant influence on the structural integrity of UO2 particles in the pellets. The sintering temperature has a significant influence on the morphology and relative density of the SiC matrix. When the relative density is lower than 95%, the sintering temperature has a greater effect on the TC of the fuel pellets; when the relative density is higher than 95%, the SiC content has a greater impact on the TC. The TC of the FCM pellets prepared in this study is increased by up to 256.6% compared with the pure UO2.